(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The innovative use of Multiregional Input-Output Tables from the Asian Development Bank inthis study makes it noteworthy. It makes an effort to investigate how trade and GDP affect exports, aswell as how employment trends and trade policies affect account balances. The study adopts a dualstrategy, combining quantitative analysis of GDP, exports, and employment with qualitative investigationof sector-specific dynamics and trade relations. This study aims to understand how the trade war hasaffected various economies. The People’s Republic of China (PRC), the United States (US), and othernations all have different economic clout, which is a result of several factors like tariff rates, marketdependence, and industrial competitiveness. The ongoing trade spat between the US and the PRC hashad negative economic effects on both countries. Trade restrictions led to GDP declines of 0.1 and0.5, respectively, in the PRC and the US. Electronics suffered the greatest, followed by a wide range ofother sectors, and the negative effects were most severe in the PRC. On the other hand, a number ofdeveloping Asian nations profited from market-competitive industries including agriculture, textiles, andelectronics. Significant employment losses might come from this scenario, especially in the People’sRepublic of China, where an increase in hostilities could lead to the loss of up to 8.5 million jobs. In theUS, there might be a loss of 180,000 jobs. These findings show how the effects of the trade war arecomplicatedly influenced by the combination of tariffs, market dependence, and sectoral inequality.